Construction of gene coexpression networks and transcriptomic analysis for Rhizobium leguminosarum - Pardo Díaz, J (2022)
Rhizobium leguminosarum is a soil bacteria which infects plants of the legume family such as peas, lentils, and beans. When associated with the plant, R. leguminosarum fixes atmospheric nitrogen (biological nitrogen fixation), producing ammonium that is assimilated by the plant, improving plant growth. This symbiotic relationship is very important for agriculture; increasing the knowledge of plant infection and nitrogen fixation processes might lead to a decrease in the use of chemical fertilisers.